DISTRIBUTION OF SILICA CONCENTRATIONS IN GARNETS OF KIMBERLITE PIPES - Feoktistov G.D.; Vladimirov B.M.; Logachev N.A. (My University, 1989)
Our study of pyrope garnets in Quaternary terrace deposits showed that the distribution of silica concentrations in them could be described by a regular second-degree trend surface when it was plotted in MgO-Al2O3 and Cr2O3-CaO coordinates. Because the rock types from which garnets entered such placers could not always be unequivocally identified, we statistically studied the chemical compositions of garnets from the Yakutian kimberlite province, whose mineral parageneses are well known from the work of Sobolev and, consequently, were able to confirm the trend of distribution of silica concentrations in these garnets, as plotted in the same coordinates. The trend of variation in silica content of garnets established by us indicates that there are higher silica concentrations not only in garnet groups whose paragenesis clearly fits the diamond-pyrope facies (pyropes from intergrowths with the Mir pipe diamonds and magnesian garnet inclusions in diamond), but also in garnet groups extracted frm rocks that quite possibly belong to this facies (garnets associated with diamonds, garnets from diamond-bearing eclogite and calcium-depleted chrome pyropes from kimberlite concentrates). Thus, our data suggest that excess silica in garnets may serve as evidence of their formation at high pressures corresponding to the diamond-pyrope depth facies. It probably is incorporated into garnets either as the Na2CaSi5O12 end member, if they also are comparatively high in Na2O (< 0.1 percent), or as the Mg3(MgSi)Si3O, if there is little admixed Na2O in them.
Keywords: Quaternary; Cenozoic::Quaternary; Кайнозой::Четвертичная